PERAN FESTIVAL DANAU SENTANI DALAM MENDUKUNG PELESTARIAN SUMBER DAYA KEBUDAYAAN LOKAL DI KABUPATEN JAYAPURA - , WILHELMINA WELIS S. RUMAROPEN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was conducted on the conservation of local culture resources in the event of Sentani Lake Festival. The objective of this study is to find out how important the role of Sentani Lake Festival in favor of the conservation of local culture resources in Jayapura Regency. This study was conducted by using a descriptive qualitative method with a combined deductive-inductive approach. Its focus is to provide a comprehensive picture of the role of Sentani Lake Festival in support of the conservation of local culture resources in Jayapura Regency. Data used in the study were primary and secondary data, where the former was collected through interview, questionnaire, and observation and the latter was collected through literature review. Instrument used in the study were check-list, interview guide, questionnaire, regional map, and other tools relevant to the study. The data collected were analyzed by using a qualitative technique. Results of the study indicate as follows: (1) The event of Sentani Lake Festival has the very important role of supporting the protection, development and utilization efforts for traditional customary, art, and cultural heritage in Jayapura Regency through cultural attraction (Cultural Show, Local Art Exhibition, Cultural Competition, Cultural Tour, Cultural Seminar), Image Builder (theme, logo, and maskot of Sentani Lake Festival related to local culture resources), Static Animator (the development of facilities and infrastructures in support of the performance of Festival, the promotion of tourism destination potential, cultural tour), Catalisator (the development of infrastructure and market for the economic product of local society in the event of Sentani Lake Festival as well as tour and travel service in providing tourism tour packages in Jayapura Regency